2018
DOI: 10.1111/aogs.13291
|View full text |Cite
|
Sign up to set email alerts
|

Preventing post‐traumatic stress disorder following childbirth and traumatic birth experiences: a systematic review

Abstract: No research has been done on primary prevention of traumatic childbirth. Research on secondary prevention of traumatic childbirth and post-traumatic stress disorder following delivery provides insufficient evidence that the described interventions are effective in unselected groups of women. In certain subgroups, results are inhomogeneous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 47 publications
(149 reference statements)
4
94
1
6
Order By: Relevance
“…The average postpartum satisfaction scores were high (92.8% scored ≥ 8), which may indicate that women two to four weeks postdelivery are really satisfied with their birth. Earlier research found that between 9% and 44% of women experienced childbirth as traumatic and 16.3% looked back negatively on their birth experience . In our study, 4.5% of women reported being less than satisfied with their birth (postpartum satisfaction score ≤ 6).…”
Section: Discussioncontrasting
confidence: 44%
“…The average postpartum satisfaction scores were high (92.8% scored ≥ 8), which may indicate that women two to four weeks postdelivery are really satisfied with their birth. Earlier research found that between 9% and 44% of women experienced childbirth as traumatic and 16.3% looked back negatively on their birth experience . In our study, 4.5% of women reported being less than satisfied with their birth (postpartum satisfaction score ≤ 6).…”
Section: Discussioncontrasting
confidence: 44%
“…This study shows that it is of importance not only to take into account the risk of medical and physical outcomes in women with a previous CD but also acting on the risk of negative birth experience, since this can have long-term implications on the woman and her family [2][3][4]. An unplanned CD is associated with negative birth experience in the 1 st birth, confirming that this group of women are a more sensitive group [5].…”
Section: Interpretationssupporting
confidence: 59%
“…Anticipating triumph and delight, most women accept the possible difficulties of labor as part of a process to achieve a positive outcome for them and their child [1]. One in 10 have a negative birth experience which can affect the everyday life of the woman and her family, impair bonding with the newborn, even prolong birth intervals and impair future fertility [2][3][4][5]. A positive childbirth experience is an important aspect of intrapartum care and is highlighted in the new World Health Organization (WHO) guideline [6].…”
Section: Introductionmentioning
confidence: 99%
“…Women and partners indicate that they want support for birth trauma (Ayers et al, 2006;Etheridge and Slade, 2017), but multilevel barriers exist to accessing perinatal mental health services (Smith et al, 2019). On an individual level, parents can lack awareness of perinatal mental health symptoms (Russell et al, 2017;Das and Hodkinson, 2019), stigma can exist around disclosing mental health concerns (NCT, 2017), and guilt at being emotionally unwell at a perceived time of happiness (Smith et al, 2019). Partners may be particularly reluctant to seek help for their own perinatal mental health (Darwin et al, 2017), and can feel unjustified talking about birth trauma when they witnessed the trauma as oppose to women who go through the physical process of birth (Etheridge and Slade, 2017).…”
Section: Introductionmentioning
confidence: 99%